Asuhan Keperawatan pada An. R dengan Bronkopneumonia di Ruang Perawatan Anak Rumah Sakit Hermina Bekasi - Nurandani, Annisa (Tamkin Jurnal Pemberdayaan Tazkia, 2024)
Bronchopneumonia or also known as Lobar Pneumonia is an inflammation of the lungs that extends to the lung parenchyma which is characterized by the presence of infiltrated patches caused by infectious agents such as bacteria, viruses, fungi or foreign bodies. In the world, as many as 740,180 children under the age of 5 years died from pneumonia in 2019. The purpose of writing is to describe nursing care for children with bronchopneumonia in the Pediatric Care Room at Hermina Bekasi Hospital. The writing method used is a case study to explore a problem by collecting in-depth data. Data collection techniques that the authors do are interviews, observation, physical examination and documentation study. The nursing diagnoses raised were ineffective airway clearance b.d airway hypersecretion, risk of infection b.d suppression of inflammatory response and risk of nutritional deficit b.d reluctance to eat. After nursing actions for 3x24 hours, all problems were resolved. Patients and families are expected to be able to prevent recurring Bronchopneumonia by keeping the environment clean and consuming healthy food and nurses are expected to have broad insight and be able to apply their knowledge to the implementation of nursing care in Children with Bronchopneumonia.